2021
DOI: 10.1186/s12935-021-01978-w
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in peripheral blood lymphocyte subset counts and functions in patients with diffuse large B cell lymphoma during chemotherapy

Abstract: Background This study aimed to analyze the lymphocyte subsets, their activities and their dynamic changes during immunochemotherapy in patients newly diagnosed with diffuse large B cell lymphoma (DLBCL). Methods Patients with DLBCL (n = 33) were included in the present study. Their peripheral lymphocyte subsets, phenotypes and functions were detected using flow cytometry. The dynamic results of lymphocyte activities were available for 18 patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
2
3
1
Order By: Relevance
“…The origin and functional mechanism of ncMO2, cDC2 and cDC3, which are DHL-related monocytes subsets, need to be further studied. Furthermore, the NK cell ratio was significantly elevated in DHL and DLBCL groups, which is different from the previous report that NK cells are subjected to exhaustion and at the low level in newly diagnosed DLBCL patients [ 37 ], further investigation should be done in the next stage with dynamic blood samples.…”
Section: Discussioncontrasting
confidence: 97%
“…The origin and functional mechanism of ncMO2, cDC2 and cDC3, which are DHL-related monocytes subsets, need to be further studied. Furthermore, the NK cell ratio was significantly elevated in DHL and DLBCL groups, which is different from the previous report that NK cells are subjected to exhaustion and at the low level in newly diagnosed DLBCL patients [ 37 ], further investigation should be done in the next stage with dynamic blood samples.…”
Section: Discussioncontrasting
confidence: 97%
“…The results indicated that NHL patients had immune-function deficiencies in their peripheral blood, suggesting an immune defect. In agreement with previous reports, the study revealed that NHL patients had significantly decreased peripheral immune-cell percentages compared with the healthy controls [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. When the immune system cannot function optimally, T and B cells fail to detect or destroy tumor cells [ 18 , 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…A similar trend was also found in anti‐ALK AAb of patients with ALCL 10 . Relapsed patients are resistant to rituximab and the function of B cells is weakly inhibited, which thus leads to increased levels of AAbs 36 …”
Section: Discussionsupporting
confidence: 71%
“…10 Relapsed patients are resistant to rituximab and the function of B cells is weakly inhibited, which thus leads to increased levels of AAbs. 36 Four AAbs (CREB1, N4BP1, DEAF1, and UBAP2) were associated with superior prognosis, and might play a role in relieving drug resistance through NF-κB signaling pathways. Cyclic adenosine monophosphate response element-binding protein 1 (CREB1) is a nuclear transcription factor that plays a crucial role in cell differentiation, F I G U R E 6 Prognostic value of CREB1 and N4BP1 proteins and mRNA in the IHC cohort (n = 55; 100�) and four DLBCL GEO data sets (n = 1598).…”
Section: Discussionmentioning
confidence: 99%